Transcriptomic analysis on susceptibility of different inbred chicken lines towards very virulent infectious bursal disease virus infection - Mohd Isa, Nor Farah; Bejo, Mohd Hair; Mat Isa, Nurulfiza; Ideris, Aini; Nair, Venugopal; Omar, Abdul Rahman (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
Previous studies have identified differential expression of immune-mediated genes related to inflammatory response in chickens with different genetic susceptibility to IBDV infections. However, the mechanisms of genetic resistance against IBD are not known. RNA sequencing through NGS technologies provide an excellent platform to study differentially expressed genes of known or unknown functions to better define mechanisms of host resistance. Therefore, this study aimed at investigating susceptibility of different inbred chicken lines toward very virulent IBDV through transcriptomic analysis. This analysis allows for quantification and comparison of gene expression. Bioinformatics analysis of this data will allow function annotation of differentially expressed genes, indicating possible roles in the response to infection. Gene of interest, virus load detection, indel, SNP and CNV between different lines and breeds will be validated using qPCR. This study is expected to provide information that able to decipher the genetic resistance of chickens towards IBDV infection.